THE UNFINISHED STRUGGLE: CHALLENGES OF ALCOHOL PROHIBITION IN GUJARAT (International Journal of Food and Nutritional Sciences, 2023)
Abstract: Gujarat, the land of Mahatma Gandhi, has upheld alcohol prohibition since its formation in 1960. The law, intended to uphold Gandhian values and promote social welfare, has encountered significant challenges over the years. The reality of prohibition presents a paradox where illicit liquor trade flourishes, governance struggles to curb violations, and the economic potential of the alcohol industry remains untapped. This paper examines the socio-economic and legal challenges associated with alcohol prohibition in Gujarat, highlighting its impact on public health, law enforcement, and underground economies. The study underscores the necessity of policy reevaluation, striking a balance between cultural ethos and pragmatic governance.